Development of fuzzy logic control system of the mobile robot - Булкин, Виталий Иванович (Eastern-European Journal of Enterprise Technologies, 2015)
A mathematical model for the mobile robot control system based on fuzzy algorithms under rapidly changing dynamic environment was developed in the paper. The mathematical model is a system of algebra-predicate equations. Based on the equations obtained, AP-structures, which are associative-logical converters (ALC), were developed. Values of membership functions of input and output linguistic variables at intermediate points in the area of the carrier of linguistic values were found. Fuzzy subsets of input and output linguistic variables are presented as corresponding equations of the predicate algebra. Based on the algebra-predicate equations, the AP-structures of recognizers of fuzzy subsets of input and output linguistic variables were constructed. When developing the knowledge base of the fuzzy logic control system for the mobile robot, production rules were formalized using the mathematical apparatus of the predicate algebra. Based on the equations obtained, the AP-structures, implementing these rules as ALC were constructed. As a result of the research, it was found that the AP-structures obtained can be reconfigured to recognize various domain objects. Therefore, such structures can be classified as flexible, reconfigurable structures of parallel data processing, operating in real time. The results obtained are important from the theoretical and practical points of view since the functional-structural method allows to develop mathematical models for the human intelligence functions in the language of predicate algebra. Based on such models, creating the AP-structures that have functional-structural similarity with the human intelligence is possible.